CDW and CDW-EIS calculations of simultaneous ionization in collisions between dressed projectiles and atomic targets. (July 2015) - Monti, J M; Fregenal, D; Fainstein, P D; Bernardi, G; Schuch, R; Suárez, S G; Rivarola, R D; Fiol, J
Synopsis: The role of simultaneous electron emission in collision between dressed ions and atoms is discussed. Methods of calculations within quantum-mechanical Continuum-Distorted- Wave (CDW) and Continuum-distorted Wave-Eikonal-Initial-State (CDW-EIS) models are revisited and improved within a semiclassical probabilistic approach.